The dawn of the future: 30 years from the first biopsy of a human embryo. The detailed history of an ongoing revolution - Danilo Cimadomo; Laura Rienzi; Antonio Capalbo; Carmen Rubio; Federica Innocenti; Carmen M. García-Pascual; Filippo Maria Ubaldi; Alan H. Handyside (2020)
Following early studies showing no adverse effects, cleavage stage biopsy by zona drilling using acid Tyrode's solution, and removal of single blastomeres for preimplantation genetic testing (PGT) and identification of sex in couples at risk of X-linked disease, was performed by Handyside and colleagues in late 1989, and pregnancies reported in 1990. This method was later used for specific diagnosis of monogenic conditions, and a few years later also for chromosomal structural and/or numerical impairments, thereby establishing a valuable alternative option to prenatal diagnosis. This revolutionary approach in clinical embryology spread worldwide, and several other embryo biopsy strategies developed over three decades in a process that is still ongoing. The rationale of this narrative review is to outline the different biopsy approaches implemented across the years in the workflow of the IVF clinics that provided PGT: their establishment, the first clinical experiences, their downsides, evolution, improvement and standardization. The history ends with a glimpse of the future: minimally/non-invasive PGT and experimental embryo micromanipulation protocols. This grand theme review outlines a timeline of the evolution of embryo biopsy protocols, whose implementation is increasing worldwide together with the increasing application of PGT techniques in IVF. It represents a vade mecum especially for the past, present and upcoming operators and experts in this field to (re)live this history from its dawn to its most likely future.